Self-medication in adult Latin American immigrants in Seville (2012)
ABSTRACT: Objective: To estimate the prevalence of non-prescription pharmaceutical use in the Latin American immigrant population. Method: A descriptive, cross-sectional study of a representative sample of 190 immigrants. We used a questionnaire based on the Behavioral Risk Factor Surveillance System (BRFSS). Results: In the past six months, 77.4% of the sample self-medicated. The prevalence of consumption of antiinflammatory and non-prescription analgesics was the highest, followed by antibiotics. A statistical difference was observed in non-prescription use of antibiotics by gender. Conclusion: The consumption of pharmaceuticals without a medical prescription in the Latin American immigrants in the city of Seville is high.